2005
DOI: 10.1029/2005ja011115
|View full text |Cite
|
Sign up to set email alerts
|

Observations of F layer electron density profiles modulated by planetary wave type oscillations in the equatorial ionospheric anomaly region

Abstract: A digital ionosonde of the type known as the Canadian Advanced Digital Ionosonde (CADI) is operational at São José dos Campos (23.2°S, 45.9°W), Brazil. This ionospheric sounding station is located under the southern crest of the ionospheric equatorial anomaly. The F layer electron density profile presents considerable day‐to‐day variability, even during undisturbed conditions, and this variability is still one of the less understood aspects of the physics of the ionosphere. The propagation of waves into the io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
56
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 31 publications
(66 reference statements)
0
56
0
Order By: Relevance
“…These waves are strongly connected with the ionospheric day-to-day variability in the equatorial and low latitudes and are important topics of investigation. Considerable research has gone into understanding the physics behind the observed high variability, particularly in the F2 layer [Fagundes et al, 2005Klausner et al, 2009;MacDougall et al, 2009;Rishbeth et al, 2009]. For many years, it was thought that during geomagnetic quiet conditions, the equatorial and low-latitude F2 layer was mainly perturbed by waves or electric fields generated by the equatorial electroject (EEJ), via tidal winds, which are transmitted along the magnetic field lines to equatorial F-region altitudes .…”
Section: Introductionmentioning
confidence: 99%
“…These waves are strongly connected with the ionospheric day-to-day variability in the equatorial and low latitudes and are important topics of investigation. Considerable research has gone into understanding the physics behind the observed high variability, particularly in the F2 layer [Fagundes et al, 2005Klausner et al, 2009;MacDougall et al, 2009;Rishbeth et al, 2009]. For many years, it was thought that during geomagnetic quiet conditions, the equatorial and low-latitude F2 layer was mainly perturbed by waves or electric fields generated by the equatorial electroject (EEJ), via tidal winds, which are transmitted along the magnetic field lines to equatorial F-region altitudes .…”
Section: Introductionmentioning
confidence: 99%
“…Ionospheric F-region parameters such as the critical frequency (foF2), minimum virtual height (h F), true height of the electron density peak (hmF2), and virtual height at a frequency of 83.4% of foF2 (hpF2 -an estimate of the true height density peak) were scaled and averaged for the 5-selected days during each month (representing a particular season). The scaling of ionograms used the software developed at Universidade do Vale do Paraíba (UNIVAP) called the UNIVAP Digital Ionosonde Data Analysis (UDIDA) (Fagundes et al, 2005). The digital ionospheric data registered by the CADIs are displayed on a PC monitor screen for scaling of ionograms.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, POLAN was run under the software UDIDA (Fagundes et al, 2005), to obtain the true height electron density profiles by conveniently choosing points in the ionograms. The profiles were calculated on an hourly basis.…”
Section: Introductionmentioning
confidence: 99%
“…Below we will not take into account the effects of viscosity, compressibility and temperature stratification [3,15,16]. Experimental verifications of existence of the magnetogradient planetary waves at the ionospheric levels are given in [7,9,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous experimental observations show [3,9,19] that in case of influence on the ionosphere from below (during the earthquakes, man-made explosions, launching of spacecrafts) and from above (during the magnetic storms, substorms, etc) planetary waves are often registered in the ionosphere. Wavelength of these waves equals or exceeds the Earth radius.…”
Section: Introductionmentioning
confidence: 99%